Parametric investigation on the thermal aspects of superconducting REBCO tapes used in CORC cables. (2021) - Ashok, K.B.; Purushothaman, Sachin J.; Jacob Thomas, Rijo; Jose Prakash, M.; Nijhuis, A.
Abstract: The primary aim of this study is to understand how the thermally induced strain varies with change in thickness of REBCO tapes. During the production stage of REBCO tapes, a residual thermal strain is induced in it due to cool down from 1020 K to 77 K. The 4 mm long and 0.091 mm thick REBCO tape cools down from 1020 K to a 0.17% residual compressive strain at room temperature and cools down to a 0.242% residual compressive strain at liquid nitrogen temperature. But these values are dependent upon the thickness of other elements in the REBCO tape. A mathematical model for the system is developed and validated using experimental data. The model is then subjected to different practical conditions and its thermal behaviour is evaluated. The performance of the superconductor is closely monitored and the degradation is determined for each case. The study has given more information on how the thermally induced strain differs with changes in thickness of REBCO tapes. The results obtained are expected to make modifications in the current production process for REBCO tapes and in its eventual usage.